Adaptive test for periodicity in restrictive EXPAR(p) models. Issue 17 (2nd September 2022) - Yousfi, A.; Merzougui, M.
Abstract: Locally asymptotically most stringent test for testing the periodicity in the restricted exponential autoregressive model EXPAR (1) has been constructed by Merzougui et al. This test is generalized here to the restricted EXPAR of order p . On the other hand, we construct a semi-parametric optimal test of periodicity when the innovation density is unknown. The sufficient conditions of the Local Asymptotic Normality ( LAN ) property are adapted to the periodic model.